2022
DOI: 10.3390/ijerph192416577
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Environmental Regulation and Fiscal Decentralization in Regional Energy Efficiency in the Context of Global Climate

Abstract: As an important factor of production, the use of energy will greatly improve production efficiency and is the material basis for China’s sustainable development. Environmental regulation plays an important role in energy efficiency (EE), while fiscal decentralization is an important institutional context for China’s economic development. In order to explore the role of environmental regulation and fiscal decentralization on EE, this paper measures the EE of 30 provincial regions in China from 2006 to 2020 by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Obviously, the results of this paper support the latter. Moderate fiscal decentralization will improve energy efficiency [24], promote the development of renewable energy [21,48], and also have spatial spillover effect [49]. This shows that fiscal decentralization will improve the positive attitude of local governments to solve energy problems.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the results of this paper support the latter. Moderate fiscal decentralization will improve energy efficiency [24], promote the development of renewable energy [21,48], and also have spatial spillover effect [49]. This shows that fiscal decentralization will improve the positive attitude of local governments to solve energy problems.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with further research, several scholars have found that the relationship between environmental regulation and energy efficiency cannot be simply explained by a linear relationship and that there may be a nonlinear relationship between them. Wu and Wang [ 18 ] calculated the energy efficiency of 30 provinces in China by using the SBM method and found that there was an inverted U-shaped relationship between environmental regulation and energy efficiency. In addition, Chu and Wang [ 19 ], by dividing environmental regulation into command-and-control and market incentive types, found that the impact of command-and-control environmental regulation on energy efficiency exhibited an inverted U shape, while that of market incentive environmental regulation exhibited a U shape.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%